2003
DOI: 10.1021/ac0343230
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Solid-Phase Microextraction Probe for in Vivo Pharmacokinetic Studies

Abstract: Simplified procedures and a reduction in sampling errors are important advantages for performing as many chemical analysis steps as possible at the site where a sample or subject is located. Solid-phase microextraction technology addresses this goal, and for our purposes, it also allows for in vivo monitoring of a dynamic living system with minimal disturbance of the system. Here we report the development of a solid-phase microextraction application for in vivo monitoring of circulating blood concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 35 publications
2
83
0
2
Order By: Relevance
“…On-site measurement cannot be applied to every target analyte due to selectivity and sensitivity issues. Prof. Pawliszyn`s group is the pioneer of in-vivo microextraction that solves this shortcoming [20]. As the name well indicates, this approach consists on the integration of sampling and microextraction and presents the following advantages: a) is faster than con-ventional approaches; b) minimizes error associated to sample treatment and c) minimizes the error associated to sample storage since the analysis is performed after the in-vivo extraction [21].…”
Section: In-vivo Microextractionmentioning
confidence: 99%
“…On-site measurement cannot be applied to every target analyte due to selectivity and sensitivity issues. Prof. Pawliszyn`s group is the pioneer of in-vivo microextraction that solves this shortcoming [20]. As the name well indicates, this approach consists on the integration of sampling and microextraction and presents the following advantages: a) is faster than con-ventional approaches; b) minimizes error associated to sample treatment and c) minimizes the error associated to sample storage since the analysis is performed after the in-vivo extraction [21].…”
Section: In-vivo Microextractionmentioning
confidence: 99%
“…The method has been successfully utilized for the in vivo and in vitro pharmacokinetic measurements of free concentrations of ligand. 113,[117][118][119][120][121][122][123][124][125] Whole-blood and free concentrations of ligand, easily measured by SPME, are of utmost importance in therapeutics, since they correlate with the pharmacological effects of drug and are more significant than plasma concentrations. Using PDMS and PA coatings, the binding of several drugs with different polarities and binding constants to human plasma and serum albumin has been determined, indicating that this method is thermodynamically sound, requiring a small volume of sample and a short analysis time.…”
Section: ·2 Ligand-receptor Binding Studymentioning
confidence: 99%
“…24,25,27,30,35,39,40,87,[117][118][119][120][121][122][123][124][125] Two configurations of proposed in vivo SPME sampling systems are illustrated (Fig. 4).…”
Section: ·4 Direct In Vivo Drug Monitoringmentioning
confidence: 99%
“…12,13 Recently, the feasibility of the method was also shown for global screening purposes. [14][15][16][17] The main advantages of in vivo SPME, being a low invasive and nondisturbing method to the system under study, were demonstrated for pharmacokinetics and metabolomics in blood, [18][19][20][21][22][23] whereas in vivo tissue analyses were conducted for analysis of pharmaceuticals in living fish. 24,25 In addition, with the SPME technique, blood sampling can be performed directly from a vein by using a hypodermic needle-assembled SPME probe (Figure 1) or by insertion of the probe to the vein through the i.v.…”
mentioning
confidence: 99%
“…catheter. 18 This approach can be successfully employed in larger animals (dogs, pigs, and so on) and humans. For small animals such as rodents, because of the small size of their vessels, a number of interfaces facilitating the use of a SPME probe were developed.…”
mentioning
confidence: 99%